2014
DOI: 10.1590/s0100-83582014000200013
|View full text |Cite
|
Sign up to set email alerts
|

Improving diquat efficacy on grasses by adding adjuvants to the spray solution before use

Abstract: -The effect of five adjuvants (non-ionic surfactant, paraffinic oil, vegetable oil, mixture of fatty acids methyl esters plus surfactant blend, and organosilicone) on diquat efficacy was assessed on poverty brome, sterile oat, and Italian ryegrass in field and pot experiments. All tank mixtures with diquat increased diquat efficacy from 50-54% to 77-98% as for fresh weight reduction, indicating significant enhancement of diquat efficacy on grasses. The increased efficacy was most likely attributed to better dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
13
0
2
Order By: Relevance
“…Reducing SST of pesticide solutions could greatly improve coverage area on target surfaces (Xu et al, 2010) and may consequently increase the performance of some pesticides. The presence of adjuvants in a spray mixture may affect pesticide deposit on the leaf surface, the transcuticular diffusion of pesticides, and effect the permeability of the plasma membrane (Wang & Liu, 2007), and may also contribute to a better retention and spread of spray solution on foliage (Gitsopoulos et al, 2014).…”
Section: Effect Of Adjuvant Concentration On Static Surface Tension Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing SST of pesticide solutions could greatly improve coverage area on target surfaces (Xu et al, 2010) and may consequently increase the performance of some pesticides. The presence of adjuvants in a spray mixture may affect pesticide deposit on the leaf surface, the transcuticular diffusion of pesticides, and effect the permeability of the plasma membrane (Wang & Liu, 2007), and may also contribute to a better retention and spread of spray solution on foliage (Gitsopoulos et al, 2014).…”
Section: Effect Of Adjuvant Concentration On Static Surface Tension Rmentioning
confidence: 99%
“…Static surface tension (SST) constitutes one of the most important properties of the spray tank mix, being able to influence the biological activity of the pesticides. Reduction of SST by adjuvants may improve the adhesion, spreading, wetting, and penetrating effects of the pesticides, as well increase translocation of the active ingredients into the plant tissues (Gimenes et al, 2013;Gitsopoulos et al, 2014;Lin et al, 2016;Zhu et al, 2018). However, attention in some circumstances is necessary, especially regarding the run-off of spray droplets that reach the leaves (Costa et al, 2015;Prado et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Correct selection of application equipment and spray adjuvants are powerful tools to maximize pesticide efficacy, reduce detrimental environmental effects and improve the economic viability of the farmer (Dorr et al, 2014). Adjuvants are used to modify the physical, biological and chemical properties of spray mixtures to improve chemical performance (Kudsk and Mathiassen, 2007) impacting on viscosity, surface tension, contac angle, droplet retention, and deposits on the target (Gitsopoulos et al, 2014;Lin et al, 2016;Stock and Brings, 2000;Wang and Liu, 2007). The adjuvants may also influence spray atomization and formation, which is important because each type of application requires a certain optimum droplet size for its biological activity (Gimenes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During disease and pest control applications, surfactant additives are commonly used to improve the efficiency of pesticides (Lin et al, 2016). Several studies showed that surfactants can greatly reduce surface tension and maximize the spread, penetration, and absorption efficacy of pesticides on leaf surfaces (Gimenes et al, 2013;Gitsopoulos et al, 2014;Lin, et al, 2016). Besides foliar uptake and biological efficacy of the active ingredients are improved with the surfactant by overlapping some leaf barriers such as cuticular membrane, trichomes and others features that decrease droplet deposition, spread and uptake of pesticide solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of herbicides can be enhanced using surfactants (Knezevic et al, 2009;Loken, HattermanValenti, 2013;Gitsopoulos et al, 2014). Enhancement of herbicidal activity by surfactants may be related to improving the dose transfer process (absorption) of active ingredient on weed leaves (McCullough, Hart, 2009).…”
Section: Introductionmentioning
confidence: 99%